Methodi Ordinatio para estudo de fumonisinas na produção de cerveja - Buczynski, Adriane (2021)
Beer is made up of water, hops, malt and yeast and is one of the most consumed beverages in the world. A problem for the brewing industry is mycotoxin contamination. These secondary metabolites produced by filamentous fungi can contaminate the raw material and consequently the beer. The levels of contamination in barley, corn and beer vary widely between different regions of the world. This study consists of a systematic review of the occurrence of fumonisins (FBs) in cereals and beer in several countries, exploring the difference in concentration in the raw material and in the final product. We also elucidate the damage caused by the addition of adjuncts and contaminated grain. The works were selected from the following databases: Science Direct, Web of Science and Scopus using the key words: fumonisin, beer, malt and brewing and their inclusion in the review was defined by the Methodi Ordinatio. Of the 22 studies on the occurrence of fumonisins, 5 did not detect the toxin, 7 detected it in samples of commercial beer and 8 in samples of beers with corn adjuncts. The countries on the African continent showed the highest levels of contamination. Among the 17 selected studies on beer processing, in 6 with the use of adjuncts of corn and sorghum, fumonisins were verified in the raw material and in the final product after processing. Our results show the needed to restrict the development of fumonisinproducing fungi in the material cousin of beer. With the theme of fumonisin control, 21 studies were selected that demonstrated conventional food processing methods are not able to eliminate the toxin, and biological control methods reduce or eliminate fumonisin. The main strategies involve adsorption methods and biodegradation enzymes.